VD_FINDINFO HC / 2014 / 407 vom 21. Mai 2014 - VD Tribunal cantonal (2014)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, INSCRIPTION, REGISTRE FONCIER | 837 al. 1 ch. 3 CC, 839 al. 2 CC, 265 al. 2 CPC (CH)